Myocardial revascularization with coronary endarterectomy. Stratification of risk factors for early mortality - Atik,Fernando Antibas (2000)
OBJECTIVE: To determine the risk factors for mortality related to myocardial revascularization when performed in association with coronary endarterectomy. METHODS: We assessed retrospectively 353 patients who underwent 373 coronary endarterectomies between January '89 and November '98, representing 3.73% of the myocardial revascularizations in this period of time. The arteries involved were as follows: right coronary artery in 218 patients (58.45%); left anterior descending in 102 patients (27.35%); circumflex artery in 39 patients (10.46%); and diagonal artery in 14 patients (3.74%). We used 320 (85.79%) venous grafts and 53 (14.21%) arterial grafts. RESULTS: In-hospital mortality among our patients was 9.3% as compared with 5.7% in patients with myocardial revascularizations without endarterectomy (p=0.003). Cause of death was related to acute myocardial infarction in 18 (54.55%) patients. The most significant risk factors for mortality identified were as follows: diabetes mellitus (p=0.001; odds ratio =7.168), left main disease (<0.001; 9.283), female sex (0.01; 3.111), acute myocardial infarction (0.02; 3.546), ejection fraction <35% (<0.001; 5.89), and previous myocardial revascularization (<0.001; 4.295). CONCLUSION: Coronary endarterectomy is related to higher mortality, and the risk factors involved are important elements of a poor outcome.